The novel HBx mutation F30V correlates with hepatocellular carcinoma in vivo, reduces hepatitis B virus replicative efficiency and enhances anti-apoptotic activity of HBx N terminus in vitro. (July 2019) - Salpini, R.; Surdo, M.; Cortese, M.F.; Palumbo, G.A.; Carioti, L.; Cappiello, G.; Spanò, A.; Trimoulet, P.; Fleury, H.; Vecchiet, J.; Pasquazzi, C.; Mirabelli, C.; et al.
Abstract: Objective: We aimed to investigate HBx genetic elements correlated with hepatitis B virus (HBV) -related hepatocellular carcinoma (HCC) and their impact on (a) HBV replicative efficiency, (b) HBx binding to circular covalently closed DNA (cccDNA), (c) apoptosis and cell-cycle progression, and (d) HBx structural stability. Methods: This study included 123 individuals chronically infected with HBV: 27 with HCC (77.9% (21/27) genotype D; 22.1% (6/27) genotype A) and 96 without HCC (75% (72/96) genotype D; 25.0% (24/96) genotype A). HepG2 cells were transfected by wild-type or mutated linear HBV genome to assess pre-genomic RNA (pgRNA) and core-associated HBV-DNA levels, HBx-binding onto cccDNA by chromatin immunoprecipitation-based quantitative assay, and rate of apoptosis and cell-cycle progression by cytofluorimetry. Results: F30V was the only HBx mutation correlated with HCC (18.5% (5/27) in HCC patients versus 1.0% (1/96) in non-HCC patients, p 0.002); a result confirmed by multivariate analysis. In vitro, F30V determined a 40% and 60% reduction in pgRNA and core-associated HBV-DNA compared with wild-type (p <0.05), in parallel with a significant decrease of HBx binding to cccDNA and decreased HBx stability. F30V also decreased the percentage of apoptotic cells compared with wild-type (14.8 ± 6.8% versus 19.1 ± 10.1%, p <0.01, without affecting cell-cycle progression) and increased the probability of HBx-Ser-31 being phosphorylated by PI3K-Akt kinase (known to promote anti-apoptotic activity). Conclusions: F30V was closely correlated with HBV-induced HCC in vivo, reduced HBV replicative efficiency by affecting HBx-binding to cccDNA and increased anti-apoptotic HBx activity in vitro . This suggests that F30V (although hampering HBV's replicative capacity) may promote hepatocyte survival, so potentially allowing persistent production of viral progeny and initiating HBV-driven hepatocarcinogenesis. Investigation of viral genetic markers associated with HCC is crucial to identify those patients at higher risk of HCC, who hence deserve intensive liver monitoring and/or early anti-HBV therapy.